The importance of public libraries in education for health literacy: A case study on diabetic patients. (October 2019) - Pirialam, Hamed; Kazerani, Maryam; Shekofteh, Maryam; Razzaghi, Zahra
Public libraries can play a major role in improving health literacy of clients by offering special services. Educating diabetic patients through public libraries can improve the dissemination of health information. The objective of the study was to evaluate the effect of education on the level of health literacy among diabetic patients referring to a public library, and the relationship between health literacy level, age and gender of patients. This research is a quasi-experimental study with pre-test and post-test. The study population included 48 diabetic patients referring to the public library. The research tool is a nationalized adult health literacy questionnaire in Iran. Results showed that 14.5% of samples had the maximum access to the required information in terms of accessibility. In terms of reading skill, 20% of samples had the maximum skill needed to read the information resources. In terms of information comprehension, 27% of samples had a maximum comprehending of the information they needed. In terms of evaluation, 13.5% of samples had completely correct evaluation of the information they needed. In terms of decision making, 24.5% of the people made decisive decisions about their information demands. The mean health literacy of diabetic patients before and after education showed a significant difference. In addition, no significant relationship was found between the level of health literacy and the age of diabetic patients referring to the public library before and after education (r <0.05). The health literacy level of diabetic patients increased before and after education in both males and females. It was concluded that as one of the tasks of public libraries is teaching citizens, the use of educational capacities in public libraries in the health sector can improve community health.